A kind of anti-corrosion strong and tough paraffin sealing film and preparation method thereof
By introducing materials such as anti -corrosion -resistant composite nano -slices and polyethylene, forming a covering layer and mesh structure, the problem of insufficient tolerance of the sealing membrane to the corrosive liquid is solved, and the effect of high secret sealing and strong toughness is achieved Essence
Patent Information
- Application Number
- CN202410647656.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-23
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-05-23
AI Technical Summary
In the prior art, the sealing film has weak resistance to corrosive liquids, resulting in poor sealing properties and unable to maintain a long-term high sealing effect.
Using materials such as corrosion -resistant composite nanoflics and polyethylene to prepare the anti -corrosion -resistant and tough paraffin sealing film through squeezing the film blowing film to form a continuous phase coverage layer to block the corrosive liquid, and the mutual insertion and more through the nanoscopic materials and more The hybridization of wall carbon nanotubes forms a mesh structure to enhance density and toughness.
It significantly enhances the blocking effect of the seal film on the corrosive liquid, improves the sealing and corrosion resistance. At the same time, it gives the seal film strong and tough, which can not break during stretching, and has the characteristics of high sealing and reused use.
Smart Images

Figure BDA0004855349490000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sealing film materials, in particular to a corrosion-resistant and strong-toughness paraffin sealing film and a preparation method thereof. Background Art
[0002] Sealing film is a special film product that can be automatically sealed, molded, and has good toughness. Sealing film is widely used in life science research laboratories such as molecular biology, cell biology, and immunology. Sealing film has high permeability, high water vapor permeability, and strong corrosion resistance. The thickness of the product is 127μm, and it is another feature of the sealing film that it can be easily tied into a "dead knot". The length of the sealing film can even be stretched to 3-4 times without breaking. The main component of this product is paraffin, which is not resistant to high temperatures. It will soften and become sticky at 65℃. It is recommended not to exceed this temperature, so it cannot be sterilized at high temperature. In addition, the sealing film can quickly and effectively seal various laboratory utensils and is easy to use. It is waterproof and moisture-proof, can effectively prevent the volatilization and contamination of experimental samples, and can effectively protect anhydrous substances.
[0003] For example, the invention patent with announcement number CN101942133A discloses a polyethylene film and a composite film with uniform heat-sealing strength. The composite film includes a surface layer, an inner layer and a barrier layer arranged between the surface layer and the inner layer. The surface layer is a biaxially oriented polypropylene film, the barrier layer is a polyester aluminum-coated film, and the inner layer includes at least a heat-sealing layer, which includes 50-70wt% of low-density polyethylene (LDPE), 20-30wt% of linear low-density polyethylene (LLDPE) and 10-20wt% of polybutene-1 (PB-1). In the above technology, the heat-sealing layer mainly utilizes the characteristics of low compatibility and easy dispersibility of PB-1 in polyethylene. After LDPE, LLDPE and PB-1 are blended, LDPE and LLDPE form a continuous polyethylene phase, and the PB-1 phase is evenly dispersed in the polyethylene phase in the form of islands. When the seal is peeled off, the interface between the polyethylene phase and the PB-1 phase is separated to achieve the opening of the seal; the composite film prepared in the above technology has a relatively uniform sealing strength after heat sealing, and the seal is easy to open or tear, but the sealing film has weak tolerance to corrosive polar substances such as salt solutions, inorganic acids, and alkaline solutions. In the sealing of corrosive liquids, the sealing is poor and cannot maintain a long-term high sealing effect. Summary of the invention
[0004] In view of the problems existing in the prior art, the object of the present invention is to provide a corrosion-resistant and strong-tough paraffin sealing film and a preparation method thereof.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A corrosion-resistant and tough paraffin sealing film, the paraffin sealing film is made of the following raw materials in parts by weight: 20-30 parts of paraffin, 10-15 parts of polyethylene, 3-6 parts of plastic additives, 2-5 parts of corrosion-resistant composite nanosheets, and 1-2 parts of lubricant;
[0007] The lubricant is at least one of Fischer-Tropsch wax, polyethylene wax and oxidized polyethylene wax.
[0008] As a further preferred embodiment of the present invention, the plastic additive includes a plasticizer, an antioxidant and a filler, and the mass ratio of the three is (2-5):1:(10-20).
[0009] As a further preferred embodiment of the present invention, the plasticizer is at least one of phthalate esters, aliphatic dibasic acid esters, and phosphate esters;
[0010] The antioxidant is at least one of butylated hydroxyanisole, dibutyl hydroxytoluene and propyl gallate;
[0011] The filler is at least one of kaolin, talcum powder and mica powder.
[0012] As a further preferred embodiment of the present invention, the preparation method of the corrosion-resistant composite nanosheet is as follows:
[0013] 1) placing the hydroxylated multi-walled carbon nanotubes in a vacuum drying oven and drying for 6-10 hours to obtain pretreated multi-walled carbon nanotubes, then dissolving 0.5-1.0 g of the pretreated multi-walled carbon nanotubes in a mixed solution consisting of 150-180 mL of ethanol and 50-70 mL of deionized water, and slowly dropping 15-18 mL of concentrated ammonia water to obtain system A, ultrasonically dispersing system A for 60-80 minutes, during the ultrasonic dispersion, dissolving 2-3 g of tetraethyl orthosilicate in 20-30 mL of ethanol, and slowly dropping it into system A, and after the ultrasonic dispersion is completed, magnetically stirring at room temperature for 18-23 hours to obtain a mixed system B;
[0014] 2) The nanosheet material is added to the mixed system B, and ultrasonic treatment is performed at 200-300W for 1-2h, and then 3-aminopropyltriethoxysilane is dissolved in a solvent consisting of equal volumes of ethanol and acetic acid, and then added to the mixed system B, and magnetic stirring is performed at room temperature for 6-10h, and then centrifugation is performed, and the obtained precipitate is repeatedly washed with anhydrous ethanol and then dried to obtain a corrosion-resistant composite nanosheet.
[0015] As a further preferred embodiment of the present invention, in step 1), the drying temperature is 60-80°C;
[0016] The power of the ultrasonic dispersion is 1000-1300W.
[0017] As a further preferred embodiment of the present invention, in step 2), the usage ratio of the nanosheet material, the mixed system B, 3-aminopropyltriethoxysilane and the solvent is (3-7) g: (180-260) mL: (0.035-0.042) g: (2-3) mL.
[0018] As a further preferred embodiment of the present invention, the preparation method of the nanosheet material is as follows:
[0019] 1) Magnesium nitrate hexahydrate and aluminum nitrate nonahydrate are sequentially added to deionized water, and stirred thoroughly to obtain solution A; sodium hydroxide and citric acid are sequentially added to deionized water, and stirred thoroughly to obtain solution B; solution A and solution B are simultaneously poured into a colloid mill in a volume ratio of 1:(1.5-1.7), and stirred at 3000-5000 r / min for 2-5 min; the formed colloidal suspension is transferred to a hydrothermal reactor, and aged at a constant temperature of 100-110° C. for 24-30 h; the obtained product is repeatedly washed with deionized water and anhydrous ethanol and then dried to obtain citric acid intercalated hydrotalcite;
[0020] 2) Add citric acid intercalated hydrotalcite and urea to deionized water, disperse at 200-300W ultrasonic for 30-50min to obtain a dispersion, then put it into a microwave oven and heat it at 800-1000W for 10-30min, take out the obtained product, heat it at 60-80°C for 3-5h, then put it in a 2.0-2.8mol / L hydrochloric acid solution for 12-16h, and obtain a nanosheet material after dialysis and centrifugation.
[0021] As a further preferred embodiment of the present invention, in step 1), in the solution A, the ratio of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, and deionized water is (0.08-0.15) mol: (0.04-0.08) mol: (100-180) mL;
[0022] In the solution B, the ratio of sodium hydroxide, citric acid and deionized water is (0.32-0.65) mol: (0.04-0.07) mol: (150-260) mL;
[0023] As a further preferred embodiment of the present invention, in step 2), the usage ratio of the deionized water, the citric acid intercalated hydrotalcite and the urea is (50-100) mL: (1-3) g: (3-7) g.
[0024] A method for preparing a corrosion-resistant and tough paraffin sealing film specifically comprises the following steps:
[0025] Prepare each component according to weight, heat the paraffin to melt it into liquid, then add polyethylene, plastic additives, corrosion-resistant composite nanosheets and lubricants in sequence, stir thoroughly and co-extrude and blow film to obtain the desired corrosion-resistant and strong paraffin sealing film.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] In the present invention, urea and citric acid are used as precursors to allow carbon nitride to grow only in the two-dimensional confined space of hydrotalcite, and after the hydrotalcite layer is removed, the ultra-thin nanosheets between the layers are released to obtain a nanosheet material. The nanosheet material is stacked on each other to form a multi-layer structure, which is introduced into the sealing film. Through the mutual intercalation between the sheets, a continuous phase covering layer can be formed in the sealing film, which plays a good barrier role and can inhibit the invasion of external corrosive liquids. At the same time, in order to further enhance the effect of the sealing film in inhibiting the invasion of external corrosive liquids, in the present invention, silicon dioxide is used to perform hybrid modification treatment on multi-walled carbon nanotubes, so as to overcome the electrostatic force and van der Waals force between the multi-walled carbon nanotubes, thereby improving the defect that the multi-walled carbon nanotubes are easy to agglomerate, so that the hybrid modified multi-walled carbon nanotubes present large sheets. The flocculent hybrid modified multi-walled carbon nanotubes can be well embedded in the multi-layered nanosheet material and form a strong bond with it. The embedded flocculent hybrid modified multi-walled carbon nanotubes can form a network structure through mutual cross-linking, which can play the role of a connecting medium, and can bring the nanosheet material closer, so that it can better produce mutual intercalation between layers. At the same time, the formation of the network structure can increase the firmness of the intercalation of the nanosheet material, so that the formed covering layer is more stable, which can significantly enhance the barrier effect against the invasion of corrosive liquids; at the same time, the network structure is formed through mutual cross-linking and is evenly distributed in the sealing film, which increases the cross-linking density inside the sealing film, so that the sealing film has strong toughness and will not break when stretched, so that it can be repeatedly folded and practical, and can also achieve high sealing when wrapped around objects with sharp shapes.
[0028] In the present invention, paraffin wax, polyethylene, etc. are used as raw materials, and the prepared corrosion-resistant composite nanosheets are introduced into the sealing film matrix, so that a continuous phase covering layer can be formed in the sealing film, which plays a good barrier role and can inhibit the invasion of external corrosive liquids. A network structure is formed by mutual cross-linking, which is evenly distributed in the sealing film, thereby increasing the cross-linking density inside the sealing film, so that the sealing film has strong toughness and will not break when stretched, so that it can be repeatedly folded and practical, and can also achieve high sealing performance when wrapped around objects with sharp shapes. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] In the embodiment of the present invention, the lubricant is Fischer-Tropsch wax; the plastic additive includes a plasticizer, an antioxidant and a filler, and the mass ratio of the three is 3:1:16, wherein the plasticizer is dioctyl phthalate; the antioxidant is butylated hydroxyanisole; and the filler is kaolin.
[0031] Example 1
[0032] A corrosion-resistant and tough paraffin sealing film, which is made of the following raw materials in parts by weight: 20 parts of paraffin, 10 parts of polyethylene, 3 parts of plastic additives, 2 parts of corrosion-resistant composite nanosheets, and 1 part of lubricant;
[0033] The preparation method of the corrosion-resistant and tough paraffin sealing film specifically comprises the following steps:
[0034] Prepare each component according to weight, heat the paraffin to melt it into liquid, then add polyethylene, plastic additives, corrosion-resistant composite nanosheets and lubricants in sequence, stir thoroughly and co-extrude and blow film to obtain the desired corrosion-resistant and strong paraffin sealing film.
[0035] The preparation method of the corrosion-resistant composite nanosheet is as follows:
[0036] 1) 0.08 mol of magnesium nitrate hexahydrate and 0.04 mol of aluminum nitrate nonahydrate were sequentially added to 100 mL of deionized water, and the mixture was stirred thoroughly to obtain solution A. 0.32 mol of sodium hydroxide and 0.04 mol of citric acid were sequentially added to 150 mL of deionized water, and the mixture was stirred thoroughly to obtain solution B. Solution A and solution B were simultaneously poured into a colloid mill at a volume ratio of 1:1.5, and stirred at 3000 r / min for 2 min. The formed colloidal suspension was transferred to a hydrothermal reactor, and the mixture was aged at a constant temperature of 100° C. for 24 h. The obtained product was repeatedly washed with deionized water and anhydrous ethanol and then dried to obtain citric acid intercalated hydrotalcite.
[0037] 2) 1 g of citric acid intercalated hydrotalcite and 3 g of urea were added to 50 mL of deionized water, and the dispersion was obtained after 200 W ultrasonic dispersion for 30 min, and then placed in a microwave oven and heated at 800 W for 10 min. The obtained product was taken out, heated at 60 ° C for 3 h, and then placed in a 2 mol / L hydrochloric acid solution for 12 h. After dialysis and centrifugation, a nanosheet material was obtained;
[0038] 3) placing the hydroxylated multi-walled carbon nanotubes in a vacuum drying oven and drying them at 60° C. for 6 h to obtain pretreated multi-walled carbon nanotubes, then dissolving 0.5 g of the pretreated multi-walled carbon nanotubes in a mixture of 150 mL of ethanol and 50 mL of deionized water, and slowly dropping 15 mL of concentrated ammonia water to obtain system A, ultrasonically dispersing system A at 1000 W for 60 min, dissolving 2 g of tetraethyl orthosilicate in 20 mL of ethanol during the ultrasonic dispersion, and slowly dropping it into system A, and after the ultrasonic dispersion, magnetically stirring at room temperature for 18 h to obtain a mixed system B;
[0039] 4) Add 3 g of the nanosheet material to 180 mL of the mixed system B, ultrasonically treat it at 200 W for 1 h, then dissolve 0.035 g of 3-aminopropyltriethoxysilane in 2 mL of a solvent consisting of equal volumes of ethanol and acetic acid, and then add it to the mixed system B, magnetically stir it at room temperature for 6 h, and then centrifuge it. The resulting precipitate is repeatedly washed with anhydrous ethanol and then dried to obtain a corrosion-resistant composite nanosheet.
[0040] Example 2
[0041] A corrosion-resistant and tough paraffin sealing film, which is made of the following raw materials in parts by weight: 25 parts of paraffin, 12 parts of polyethylene, 5 parts of plastic additives, 3 parts of corrosion-resistant composite nanosheets, and 1.5 parts of lubricant;
[0042] The preparation method of the corrosion-resistant and tough paraffin sealing film specifically comprises the following steps:
[0043] Prepare each component according to weight, heat the paraffin to melt it into liquid, then add polyethylene, plastic additives, corrosion-resistant composite nanosheets and lubricants in sequence, stir thoroughly and co-extrude and blow film to obtain the desired corrosion-resistant and strong paraffin sealing film.
[0044] The preparation method of the corrosion-resistant composite nanosheet is as follows:
[0045] 1) 0.12 mol of magnesium nitrate hexahydrate and 0.06 mol of aluminum nitrate nonahydrate were sequentially added to 150 mL of deionized water, and the mixture was stirred thoroughly to obtain solution A. 0.46 mol of sodium hydroxide and 0.05 mol of citric acid were sequentially added to 230 mL of deionized water, and the mixture was stirred thoroughly to obtain solution B. Solution A and solution B were simultaneously poured into a colloid mill at a volume ratio of 1:1.6, and stirred at 4000 r / min for 3 min. The formed colloidal suspension was transferred to a hydrothermal reactor, and aged at a constant temperature of 105° C. for 26 h. The obtained product was repeatedly washed with deionized water and anhydrous ethanol and then dried to obtain citric acid intercalated hydrotalcite;
[0046] 2) Add 2 g of citric acid intercalated hydrotalcite and 5 g of urea to 70 mL of deionized water, disperse at 260 W ultrasonically for 40 min to obtain a dispersion, then put it into a microwave oven and heat it at 900 W for 20 min. Take out the obtained product, heat it at 70 ° C for 4 h, and then place it in a 2.5 mol / L hydrochloric acid solution for 15 h. After dialysis and centrifugation, a nanosheet material is obtained;
[0047] 3) placing the hydroxylated multi-walled carbon nanotubes in a vacuum drying oven and drying at 70° C. for 8 h to obtain pretreated multi-walled carbon nanotubes, then dissolving 0.8 g of the pretreated multi-walled carbon nanotubes in a mixture of 170 mL of ethanol and 60 mL of deionized water, and slowly dropping 17 mL of concentrated ammonia water to obtain system A, ultrasonically dispersing system A at 1200 W for 70 min, during the ultrasonic dispersion, dissolving 2.5 g of tetraethyl orthosilicate in 25 mL of ethanol and slowly dropping it into system A, and after the ultrasonic dispersion, magnetically stirring at room temperature for 20 h to obtain a mixed system B;
[0048] 4) Add 5 g of the nanosheet material to 210 mL of the mixed system B, ultrasonically treat it at 260 W for 1.5 h, then dissolve 0.038 g of 3-aminopropyltriethoxysilane in 2.5 mL of a solvent consisting of equal volumes of ethanol and acetic acid, and then add it to the mixed system B, magnetically stir it at room temperature for 8 h, and then centrifuge it. The precipitated material is repeatedly washed with anhydrous ethanol and then dried to obtain a corrosion-resistant composite nanosheet.
[0049] Example 3
[0050] A corrosion-resistant and tough paraffin sealing film, which is made of the following raw materials in parts by weight: 30 parts of paraffin, 15 parts of polyethylene, 6 parts of plastic additives, 5 parts of corrosion-resistant composite nanosheets, and 2 parts of lubricants;
[0051] The preparation method of the corrosion-resistant and tough paraffin sealing film specifically comprises the following steps:
[0052] Prepare each component according to weight, heat the paraffin to melt it into liquid, then add polyethylene, plastic additives, corrosion-resistant composite nanosheets and lubricants in sequence, stir thoroughly and co-extrude and blow film to obtain the desired corrosion-resistant and strong paraffin sealing film.
[0053] The preparation method of the corrosion-resistant composite nanosheet is as follows:
[0054] 1) 0.15 mol of magnesium nitrate hexahydrate and 0.08 mol of aluminum nitrate nonahydrate were sequentially added to 180 mL of deionized water, and the mixture was stirred thoroughly to obtain solution A. 0.65 mol of sodium hydroxide and 0.07 mol of citric acid were sequentially added to 260 mL of deionized water, and the mixture was stirred thoroughly to obtain solution B. Solution A and solution B were simultaneously poured into a colloid mill at a volume ratio of 1:1.7, and stirred at 5000 r / min for 5 min. The formed colloidal suspension was transferred to a hydrothermal reactor, and aged at a constant temperature of 110° C. for 30 h. The obtained product was repeatedly washed with deionized water and anhydrous ethanol and then dried to obtain citric acid intercalated hydrotalcite;
[0055] 2) Add 3 g of citric acid intercalated hydrotalcite and 7 g of urea to 100 mL of deionized water, disperse at 300 W ultrasonically for 50 min to obtain a dispersion, then put it into a microwave oven and heat it at 1000 W for 30 min. Take out the obtained product, heat it at 80 ° C for 5 h, and then place it in a 2.8 mol / L hydrochloric acid solution for 16 h. After dialysis and centrifugation, a nanosheet material is obtained;
[0056] 3) placing the hydroxylated multi-walled carbon nanotubes in a vacuum drying oven and drying them at 80° C. for 10 h to obtain pretreated multi-walled carbon nanotubes, then dissolving 1 g of the pretreated multi-walled carbon nanotubes in a mixture of 180 mL of ethanol and 70 mL of deionized water, and slowly dropping 18 mL of concentrated ammonia water to obtain system A, ultrasonically dispersing system A at 1300 W for 80 min, dissolving 3 g of tetraethyl orthosilicate in 30 mL of ethanol during the ultrasonic dispersion, and slowly dropping it into system A, and after the ultrasonic dispersion, magnetically stirring at room temperature for 23 h to obtain a mixed system B;
[0057] 4) Add 7 g of the nanosheet material to 260 mL of the mixed system B, ultrasonically treat it at 300 W for 2 h, then dissolve 0.042 g of 3-aminopropyltriethoxysilane in 3 mL of a solvent consisting of equal volumes of ethanol and acetic acid, and then add it to the mixed system B, magnetically stir it at room temperature for 10 h, and then centrifuge it. The resulting precipitate is repeatedly washed with anhydrous ethanol and then dried to obtain a corrosion-resistant composite nanosheet.
[0058] Comparative Example 1: This comparative example is basically the same as Example 1, except that it does not contain corrosion-resistant composite nanosheets.
[0059] Comparative Example 2: This comparative example is basically the same as Example 1, except that step 1) is omitted in the preparation of the corrosion-resistant composite nanosheets.
[0060] Comparative Example 3: This comparative example is basically the same as Example 1, except that in the preparation of the corrosion-resistant composite nanosheets, steps 1)-2) are omitted.
[0061] Comparative Example 4: This comparative example is basically the same as Example 1, except that step 3) is omitted in the preparation of the corrosion-resistant composite nanosheets.
[0062] Comparative Example 5: This comparative example is basically the same as Example 1, except that in the preparation of the corrosion-resistant composite nanosheets, steps 3)-4) are omitted.
[0063] Test experiment:
[0064] The sealing film samples were processed by the methods provided in Examples 1-3 and Comparative Examples 1-5, and then immersed in a 22 wt % sodium hydroxide solution for 48 h. The sealing film was then taken out and the damage on its surface was observed. The results are shown in Table 1.
[0065] Table 1
[0066]
[0067] It can be seen from the above table that the paraffin sealing film in the present invention has good corrosion resistance, can be well used in experiments, medical treatment and other places, and can well seal corrosive substances.
[0068] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A corrosion-resistant and tough paraffin sealing film, characterized in that: The paraffin sealing film is made of the following raw materials in parts by weight: 20-30 parts of paraffin, 10-15 parts of polyethylene, 3-6 parts of plastic additives, 2-5 parts of corrosion-resistant composite nanosheets, and 1-2 parts of lubricant; the lubricant is at least one of Fischer-Tropsch wax, polyethylene wax, and oxidized polyethylene wax; The preparation method of the corrosion-resistant composite nanosheet is as follows: 1) placing the hydroxylated multi-walled carbon nanotubes in a vacuum drying oven and drying for 6-10 hours to obtain pretreated multi-walled carbon nanotubes, then dissolving 0.5-1.0 g of the pretreated multi-walled carbon nanotubes in a mixed solution consisting of 150-180 mL of ethanol and 50-70 mL of deionized water, and slowly dropping 15-18 mL of concentrated ammonia water to obtain system A, ultrasonically dispersing system A for 60-80 minutes, during the ultrasonic dispersion, dissolving 2-3 g of tetraethyl orthosilicate in 20-30 mL of ethanol, and slowly dropping it into system A, and after the ultrasonic dispersion is completed, magnetically stirring at room temperature for 18-23 hours to obtain a mixed system B; 2) The nanosheet material is added to the mixed system B, and ultrasonic treatment is performed at 200-300W for 1-2h, and then 3-aminopropyltriethoxysilane is dissolved in a solvent consisting of equal volumes of ethanol and acetic acid, and then added to the mixed system B, and magnetic stirring is performed at room temperature for 6-10h, and then centrifugation is performed, and the obtained precipitate is repeatedly washed with anhydrous ethanol and then dried to obtain a corrosion-resistant composite nanosheet.
2. The corrosion-resistant and tough paraffin sealing film according to claim 1, characterized in that: The plastic additives include plasticizers, antioxidants and fillers, and the mass ratio of the three is (2-5):1:(10-20).
3. The corrosion-resistant and tough paraffin sealing film according to claim 2, characterized in that: The plasticizer is at least one of phthalate, aliphatic dibasic acid ester and phosphate; The antioxidant is at least one of butylated hydroxyanisole, dibutyl hydroxytoluene and propyl gallate; The filler is at least one of kaolin, talcum powder and mica powder.
4. The corrosion-resistant and tough paraffin sealing film according to claim 1, characterized in that: In step 1), the drying temperature is 60-80°C; the power of the ultrasonic dispersion is 1000-1300W.
5. The corrosion-resistant and tough paraffin sealing film according to claim 1, characterized in that: In step 2), the ratio of the amount of the nanosheet material, the mixed system B, 3-aminopropyltriethoxysilane, and a solvent consisting of equal volumes of ethanol and acetic acid is (3-7) g: (180-260) mL: (0.035-0.042) g: (2-3) mL.
6. The corrosion-resistant and tough paraffin sealing film according to claim 1, characterized in that: The preparation method of the nanosheet material is as follows: 1) Magnesium nitrate hexahydrate and aluminum nitrate nonahydrate are sequentially added to deionized water, and stirred thoroughly to obtain solution A; sodium hydroxide and citric acid are sequentially added to deionized water, and stirred thoroughly to obtain solution B; solution A and solution B are simultaneously poured into a colloid mill in a volume ratio of 1:(1.5-1.7), and stirred at 3000-5000 r / min for 2-5 min; the formed colloidal suspension is transferred to a hydrothermal reactor, and aged at a constant temperature of 100-110° C. for 24-30 h; the obtained product is repeatedly washed with deionized water and anhydrous ethanol and then dried to obtain citric acid intercalated hydrotalcite; 2) Add citric acid intercalated hydrotalcite and urea to deionized water, disperse at 200-300W ultrasonic for 30-50min to obtain a dispersion, then put it into a microwave oven and heat it at 800-1000W for 10-30min, take out the obtained product, heat it at 60-80°C for 3-5h, then put it in a 2.0-2.8mol / L hydrochloric acid solution for 12-16h, and obtain a nanosheet material after dialysis and centrifugation.
7. The corrosion-resistant and tough paraffin sealing film according to claim 6, characterized in that: In step 1), in the solution A, the ratio of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, and deionized water is (0.08-0.15) mol: (0.04-0.08) mol: (100-180) mL; In the solution B, the usage ratio of sodium hydroxide, citric acid and deionized water is (0.32-0.65) mol: (0.04-0.07) mol: (150-260) mL.
8. The corrosion-resistant and tough paraffin sealing film according to claim 6, characterized in that: In step 2), the usage ratio of deionized water, citric acid intercalated hydrotalcite and urea is (50-100) mL: (1-3) g: (3-7) g.
9. A method for preparing a corrosion-resistant and tough paraffin sealing film according to any one of claims 1 to 8, characterized in that: The specific steps include: Prepare each component according to weight, heat the paraffin to melt it into liquid, then add polyethylene, plastic additives, corrosion-resistant composite nanosheets and lubricants in sequence, stir thoroughly and co-extrude and blow film to obtain the desired corrosion-resistant and strong paraffin sealing film.
Citation Information
Patent Citations
Polyethylene film and laminated film with even heat-seal strength
CN101942133A
Thermoplastic elastic self-sealing film and preparation method thereof
CN101831106A
Sealing film and preparation method and application thereof
CN117924951A